PERFECTION OF PAPER TRANSPORTATION SETTINGS TO GET PROPERTIES ON MACHINE KOMORI LITHRONE G40 - Widya Retno Wulan; Soebardianto Soebardianto; Heni Heni (Kreator, 2019)
The perfection of the paper transportation settings raised in the Final Project work aims to achieve print accuracy, the benchmark for print accuracy is the achievement of perfection of print ink stacks on the printed results guided by the register point / print mark. Overview of the need for paper transport settings so that the printing process can run smoothly. In making this final project, the author uses a descriptive method, namely a method that explains and explains about paper transportation. The formulation of the problem that is taken in this final project is how to set up paper transportation, problems that arise during paper transportation, and solutions that can be done to overcome these problems. In this paper, the authors use literature review, field observations, and interviews related to data. From the results of these observations, it can be shown that the problems that occur at the time are caused by paper transportation settings that are not in accordance with standard work procedures. Suggestions put forward by the authors need to apply standardization of settings and provision of training for each operator who worksKeywords— Paper transport, print accuracy, tuning